Analisis Penggunaan Diksi dan Framing Pada Media massa BBC News: Teori Hegemoni Gramsci - Puri, Diah Ryscha; Canda, Elis; Chairunisa, Hera; Indhira, Indhira; Pasaribu, Parlindungan; Silalahi, Selvina; Deo, Yohanna (CV. ITTC INDONESIA, 2024)
This study aims to analyze the use of diction and framing in the news text